2016
DOI: 10.1128/jb.00220-16
|View full text |Cite
|
Sign up to set email alerts
|

CodY-Dependent Regulation of Sporulation in Clostridium difficile

Abstract: Clostridium difficile must form a spore to survive outside the gastrointestinal tract. The factors that trigger sporulation in C. difficile remain poorly understood. Previous studies have suggested that a link exists between nutritional status and sporulation initiation in C. difficile. In this study, we investigated the impact of the global nutritional regulator CodY on sporulation in C. difficile strains from the historical 012 ribotype and the current epidemic 027 ribotype. Sporulation frequencies were incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 95 publications
(158 reference statements)
2
113
0
Order By: Relevance
“…Those results (23), obtained using C. difficile codY-null mutants, established that strain variations in the CodY regulation of sporulation can occur even within a clostridial species. Therefore, given the critical role of CodY in C. perfringens type A food poisoning, an isogenic codY-null mutant of SM101, which is a transformable derivative of C. perfringens food-poisoning strain NCTC8798, was generated in the current study (25) to determine whether CodY represses sporulation in this strain as it does in CN3718 (17).…”
Section: Figmentioning
confidence: 71%
See 3 more Smart Citations
“…Those results (23), obtained using C. difficile codY-null mutants, established that strain variations in the CodY regulation of sporulation can occur even within a clostridial species. Therefore, given the critical role of CodY in C. perfringens type A food poisoning, an isogenic codY-null mutant of SM101, which is a transformable derivative of C. perfringens food-poisoning strain NCTC8798, was generated in the current study (25) to determine whether CodY represses sporulation in this strain as it does in CN3718 (17).…”
Section: Figmentioning
confidence: 71%
“…CodY was first reported to repress sporulation in Bacillus subtilis (24). Recently, the role of CodY in regulating sporulation in Clostridium species has also come under study (17,23). Our group demonstrated that CodY represses sporulation in C. perfringens type D strain CN3718 (17).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Isolates D and E1 also shared an SNV in the oligotransport-ATP binding domain of oppF (Table 4), which belongs to an operon of oligopeptide permease (opp) genes that are involved in regulating sporulation (among other processes) in some species of Bacillus and Clostridium (18,19). In vitro sporulation studies on all isolates revealed no significant difference (data not shown) in the rate of sporulation between isolate D and E1 and all other isolates.…”
Section: Discussionmentioning
confidence: 99%